Retenção de conhecimento tecnológico nas organizações como fator propulsor para o processo de inovação: estudo de caso na Batávia S/A - Helmann, Caroline Lievore (2007)
At the age of information, knowledge has become one of the most valuable resources for organizations that intend having the upperhand in competition. In the same way, the effect that the innovations have been showing in the dairy market confirms the demand of enterprises for managing and keeping their knowledge with the intention of promoting innovations by the use of quick and efficient processes. The maintenance of the specialists’ knowledge in the organization is seen as one of the factors that most have an impact on the development of new products. However, retaining people’s knowledge is a way of intensifying and improving the enterprise’s results. The present research aims to identify the practice of Knowledge Management that most contribute for the process of knowledge retention and that ease the processes of innovation. The identification of such practices was enabled through a case study conducted Batávia S/A Indústria de Alimentos, located in the city of Carambeí, state of Paraná. The company has strong presence on the Brazilian dairy market, was considered one of the most innovative enterprises of the country and uses innovations as its strategies of competitiveness. A prior research, conducted with six specialists in the area of Knowledge Management, a systematic observation, consultation of the company’s records and documents and the application of surveys and interviews have been used as the methodological procedure. The surveys were composed of 80 asserts concerning the retention of knowledge and innovation, divided into 18 practices of Knowledge Management. These aforementioned surveys were applied to six individuals who are connected to the P&D and Marketing Department and who opinioned concerning the contribution of each practice to the processes of knowledge retention and innovation. The interviews, which were semi structured, were conducted with 4 employees in order to go deep in the results obtained with the questionnaire. Among the practices that most contribute to the factor of knowledge retention in the company are the Mapping out of Knowledge, Corporative Education, Forums or Discussion Lists, Learned Lessons, Better Practices and Organizational Memory. Concerning the fact of innovation, the practices that most contribute are Management of Intellectual Capital, Learned Lessons, Corporative Education, Mapping out of Processes and Better. The identification of practices that promote the retention of knowledge and ease the processes of innovation is the first step for the enterprises to establish tools that are appropriate and practical to their strategies and employees. Although these results cannot be generalized for other enterprises, they may guide new researches in the area.